Discourse features of english texts describing endangered wild mammals - Nguyễn,Thị Tâm Nguyên (2016)
This thesis is aimed at examining discourse features of English Texts Describing Endangered Wild Mammals (ETEMs). The data for analysis in this thesis are forty-six samples of ETEMs ranging from 300 to 700 words. These samples were collected from the three official websites of reputational organizations which are founded in the United States namely U.S. Fish and Wildlife Service (FWS), Environmental Conservation Online System (ECOS), Encyclopedia of Life (EOL). The thesis was carried out based on a combination of a variety of methods such as descriptive, analytic and inductive ones. The thesis focused on analyzing discourse features of ETEMs in terms of their layout, syntactic structures, lexical choices and cohesive devices. The findings showed that the layout of ETEMs displayed a three-part structure: Headline, Illustration and Body Copy which attracts the readers’ attention to focused information. The syntactic structures were illuminated through phrases, the use of relative clauses and the passive voice. This makes strong impressions and emphasis on what the ETEMs tend to focus on. Also, the use of descriptive adjectives, compounds and nouns denoting mammals’ names makes the ETEMs more appealing and persuasive. In addition, the investigation of cohesive devices revealed that reference, conjunction, ellipsis and lexical cohesion are the devices employed with high frequencies. It is hoped that the results of this thesis can be beneficial for the teaching and learning of English language. This thesis may also be helpful for the readers in getting the detailed information of endangered mammals and appealing to the protection of the endangered wild mammals